Assessing the relationship between dietary pattern and Menopausal quality of life among euthyroid and hypothyroid disorder perimenopausal women. - Prakash, Shanthini Priya; Silambu Selvi Kumbamoorthy (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Thyroid disorders are found to be the most common endocrine disorders among women in India. Perimenopause women during the transition through menopause experience specific symptoms such as mood swings, hot flashes, sleep disturbances, forgetfulness, weight gain and vaginal dryness. These symptoms disturb the perimenopausal women’s day-to-day life and lead to a decrease in the quality of life (QoL). Aim: To assess the relationship between dietary pattern and QoL among euthyroid and hypothyroid perimenopausal women. Methods: This community-based cross-sectional study comprised 96 perimenopausal women participants among them 54 had euthyroid and 42 had the hypothyroid condition. This study was conducted in a selected area of Chengalpattu district, Tamil Nadu, India between January 2022 and April 2022. A standardized Menopause Quality of Life questionnaire (MENQOL) tool was used to assess their QoL and the dietary pattern was analyzed using 24 hr recall method. Data were analyzed statistically. Results: The dietary pattern of the euthyroid group (18.5%) was good compared to the hypothyroid group (9.5%). The QoL of the euthyroid group (41.7%) was more normal than the hypothyroid group (14.7%). The correlation was found to be positive (R= 0.468) and the test was significant (P < 0.01). Conclusion: This study concluded that there is a positive relationship between the dietary pattern and QoL among perimenopausal women having thyroid dysfunction.